Overview of air pollution and endocrine disorders - Darbre PD (International Journal of General Medicine, 2018)
Philippa D Darbre School of Biological Sciences, University of Reading, Reading, UK Abstract: Over recent years, many environmental pollutant chemicals have been shown to possess the ability to interfere in the functioning of the endocrine system and have been termed endocrine disrupting chemicals (EDCs). These compounds exist in air as volatile or semi-volatile compounds in the gas phase or attached to particulate matter. They include components of plastics (phthalates, bisphenol A), components of consumer goods (parabens, triclosan, alkylphenols, fragrance compounds, organobromine flame retardants, fluorosurfactants), industrial chemicals (polychlorinated biphenyls), products of combustion (polychlorinated dibenzodioxins/furans, polyaromatic hydrocarbons), pesticides, herbicides, and some metals. This review summarizes current knowledge concerning the sources of EDCs in air, measurements of levels of EDCs in air, and the potential for adverse effects of EDCs in air on human endocrine health. Keywords: air pollution, endocrine disruptors, particulate matter